PENGARUH ASUPAN AIR PUTIH TERHADAP BERAT BADAN REMAJA : Studi Literatur - Apriliana Apriliana (Jurnal Kesehatan, 2024)
This study aims to investigate the effect of water intake on body weight and the factors that influence this relationship. Through a comprehensive literature study and careful data analysis, this research aims to provide a better understanding of the importance of water intake in maintaining healthy body weight and preventing obesity. By considering the existing theoretical basis and previous findings, this study designed an appropriate research method to test the research hypothesis. Data is collected through surveys and observations, then analyzed using appropriate statistical techniques. The findings from this study were interpreted and concluded to provide deeper insight into the influence of water intake on body weight as well as its practical implications in a public health context. It is hoped that the results of this research can make a significant contribution to understanding and treating the problem of obesity and its related diseases.